Autophagy-Based Hypothesis on the Role of Brain Catecholamine Response During Stress - Limanaqi, Fiona; Busceti, Carla Letizia; Biagioni, Francesca; Fornai, Francesco; Puglisi-Allegra, Stefano (Frontiers in Psychiatry, 2020)
Stressful events, similar to abused drugs, significantly affect the homeostatic balance of the catecholamine brain systems while activating compensation mechanisms to restore balance. In detail, norepinephrine (NE)- and dopamine (DA)-containing neurons within the locus coeruleus (LC) and ventral tegmental area (VTA), are readily and similarly activated by psychostimulants and stressful events involving neural processes related to perception, reward, cognitive evaluation, appraisal, and stress-dependent hormonal factors. Brain catecholamine response to stress results in time-dependent regulatory processes involving mesocorticolimbic circuits and networks, where LC-NE neurons respond more readily than VTA-DA neurons. LC-NE projections are dominant in controlling the forebrain DA-targeted areas, such as the nucleus accumbens (NAc) and medial pre-frontal cortex (mPFC). Heavy and persistent coping demand could lead to sustained LC-NE and VTA-DA neuronal activity, that, when persisting chronically, is supposed to alter LC-VTA synaptic connections. Increasing evidence has been provided indicating a role of autophagy in modulating DA neurotransmission and synaptic plasticity. This alters behavior, and emotional/cognitive experience in response to drug abuse and occasionally, to psychological stress. Thus, relevant information to address the role of stress and autophagy can be drawn from psychostimulants research. In the present mini-review we discuss the role of autophagy in brain catecholamine response to stress and its dysregulation. The findings here discussed suggest a crucial role of regulated autophagy in the response and adaptation of LC-NE and VTA-DA systems to stress.